EGO DEFENSE MECHANISM OF THE MAIN FEMALE CHARACTERS IN MALEFICENT MOVIE - Nurul Khoirunisa; Endang Yuliani Rahayu (Universitas Stikubank (UNISBANK) Semarang, 2020)
This study aims to explain the causes of the main female character conflicts, the effects of the conflicts experienced by the main female character and also Ego defense mechanism performed by the main female character in the Maleficent’ s movie. This data was taken from Movie script. The author examines the dialogue and the scene. The view of ego defense found in the Maleficent's movie is well supported in literary criticism, but the discussion focuses on ego defense on Maleficent's character as seen in striking behavior with a revenge plan in the film, namely the curse of Steffan's daughter named Aurora. The theory used in this study is psychological approaches by Sigmund Freud. Meanwhile, qualitative descriptive method is used in the study with the implementation of Ego Defense Mechanism theories. Results showed that in terms of importance, Maleficent was categorized as the main female character. Also, the causes of the main female character conflicts are about disappointment has been betrayed by Steffan. Second, the effect of the conflicts experienced by the main female character is Maleficent curses Aurora as revenge to Steffan because he cuts off both wings. Third, Maleficent changes her characters become good characters because she realizes that she sincerely loves Aurora. Also, there are two ego defense mechanisms she used include projection and repression. Key Words: Ego Defense Mechanism, Sigmund Freud theories, Revenge, Maleficent character conflict.